Smart Automation for Enhanced Lighting through Remote Control Systems in Coal Mining Areas - Rizqi Pratama; Muhammad Fachri Maulana; Aan Ardyantoro (Riviera Publishing, 2024)
The coal mining industry faces significant safety challenges due to hazardous working environments and manual monitoring processes, particularly involving Tower Lamp units. These activities expose employees to risks, including harsh weather and operational incidents, leading to potential accidents and financial losses. This study proposes an intelligent safety control system employing real-time remote monitoring technology to mitigate these risks. The system enables centralized control of Tower Lamps, reducing manual interactions, improving energy efficiency through automated lighting adjustments, and enhancing workplace safety. The methodology includes designing and implementing a monitoring system with remote control capabilities supported by real-time data analysis. Expected outcomes include reduced work accidents, optimized lighting management, and streamlined operations, showcasing a scalable model for broader industrial applications. This technological innovation demonstrates a practical solution for improving safety and operational efficiency in coal mining environments.